Implementasi Pendidikan Agama Islam Dalam Membentuk Karakter Islami Siswa - Iswanto; Eva Nurazizah; Amanda Dewi Nadila; Muhammad Sultan Nur S (STIT Syekh Muhammad Nafis Tabalong, 2023)
Islamic religious education is a branch of education that focuses on learning the concept of spirituality and a divine approach based on two main laws, namely the Al-Quran and Hadith. Islam makes character or moral values an important teaching that should be the identity of every Muslim and Muslimah. Meanwhile, the implementation of PAI in learning is aimed at paying attention to morals and attitudes that can later form students' Islamic character. This article contains an explanation of the implementation of Islamic religious education which concretely affects the development of students' Islamic character at the school level and the factors that influence the success or failure of the implementation of Islamic religious education in shaping Islamic character as seen by Pondok Pesantren Darul Ikhlas. This article aims to increase understanding and implementation of Islamic religious education that can concretely influence the formation of Islamic character. This article is examined in the form of qualitative methods through interviews, documentation, and observations which are then compiled according to critical analysis so that appropriate data is obtained. The results of the research itself get a positive impression of the success of the school under study in shaping students' Islamic character through the proper implementation of Islamic religious education.